Preclinical characterization of CPL304110 as a potent and selective inhibitor of fibroblast growth factor receptors 1, 2, and 3 for gastric, bladder, and squamous cell lung cancer - Popiel, Delfina; Stańczak, Aleksandra; Skupińska, Monika; Mikołajczyk, Agata; Stańczak, Paulina; Mituła, Filip; Hucz-Kalitowska, Joanna; Jastrzębska, Kinga; Smuga, Damian; Dominowski, Jakub; Delis, Monika; Mulewski, Krzysztof; et al. (Frontiers in Oncology, 2024)
Fibroblast growth factor receptors (FGFRs) are a family of receptor tyrosine kinases expressed on a plethora of cell membranes. They play crucial roles in both embryonic development and adult tissue functions. There is an increasing amount of evidence that FGFR-mediated oncogenesis is mainly related to gene amplification, activating mutations, or translocation in tumors of various histological types. Dysregulation of FGFRs has been implicated in a wide variety of neoplasms, such as bladder, gastric, and lung cancers. Due to their functional importance, FGFRs have been considered promising drug targets for the therapy of various cancers. Multiple small-molecule inhibitors targeting this family of kinases have been developed so far. At the moment, there are two FDA-approved FGFR inhibitors, erdafitinib, and pemigatinib, for the therapy of FGFR-aberrant solid tumors.Here we presented an innovative, highly potent FGFR1-3 kinase inhibitor with excellent biological activity in vitro. CPL304110 (CPL110) selectively inhibited the growth of tumor cell lines with active FGFR signaling compared with cell lines lacking FGFR aberrations (FGFR1, 2, and 3). The effectiveness of the developed inhibitor was also demonstrated in vivo with FGFR-dependant cell lines and patient-derived tumor xenograft (PDTX) models. Positive results of preclinical analyses allowed the initiation of Phase I clinical trial (01FGFR2018; NCT04149691) for further evaluation of CPL304110 as a novel anticancer therapy.